Pengaruh Penilaian Prestasi Kerja terhadap Kinerja Karyawan pada CV Lima Citra Perdana Medan - Rendy Mario Yoshua; Rismawati Rismawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Human resources are a very important aspect for the journey of an organization, both private organizations and government organizations, to achieve the goals of the organization. Employee Performance Appraisal is an important part of all employee performance. Work Performance Assessment must be carried out formally based on criteria that are applied rationally and objectively and documented systematically, so that the interests of the employees and the company can be met. The form of this research used is associative research with a quantitative approach. The sampling technique in this study was carried out using the Nonprobability Sampling technique and used 70 respondents as the sample. Primary data in this study were obtained through distributing questionnaires and secondary data obtained through literature studies in the form of relevant books, journals and previous research. The data analysis method used is validity test, reliability test, classic assumption test, simple linear regression analysis, and instrument test. The results of the study show that performance appraisal has a positive and significant effect on employee performance. The tcount value for the work performance variable is 9.353 with a significance of 0.026. Meanwhile ttable at α=0.05 is 1.995. This shows that tcount (9.535) > ttable (1.995) and a probability value of 0.000 <0.05 then Ha is accepted so Ho is rejected. With a good work performance assessment, it will improve employee performance to work at CV Lima Citra Perdana Medan.